“FATHERING JAPAN” :DISKURSUS ALTERNATIF DALAM HEGEMONI KETIDAKSETARAAN GENDER DI JEPANG - Yusy Widarahesty (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2018)
The phenomenon of gender gap in Japan has brought many impacts of change in Japan from the declining birth rate and including the emergence of non-profit organizations (NPO) action groups namely